Learning theories for teachers - Bigge, Morris L.; Shermis, S. Samuel (Boston : Pearson/Allyn and Bacon, 2004)
This text provides a comprehensive, manageable overview of current major educational psychological theories and issues and analyzes the implications for the teaching process. Adopting the idea that "there are no final answers to questions concerning school learning," this text encourages teachers to develop their own learning theories and test them in terms of classroom reactions, structure, and the adequacy of supporting evidence." Learning Theories for Teachers" enables student teachers to use learning theory to better understand their students and alter teaching methods accordingly.
Includes bibliographical references and index.
Keywords: Learning; Cognitive learning; Effective teaching